Integrating Islamic Economic Values into the Pentahelix Model for Developing a Sustainable Digital Entrepreneurship Ecosystem - Haqiqotus Sa’adah; Siswanto (IQTISHODUNA: Jurnal Ekonomi Islam, 2025)
This study examines how Islamic economic principles may be put into practice in the Pentahelix partnership (academia, business, government, community, and media) to create a long-lasting digital entrepreneurship ecosystem. Utilizing a qualitative multi-case approach, we analyze two MSMEs in East Java Kapiten Nusantara (pesantren-based) and Superheru Snack Factory (community-based) using in-depth interviews, participant observation, and documentation. review, then Miles–Huberman cross-case analysis and methodological triangulation. According to the results, digital methods (content/community-based marketing, online marketplaces, promotion, matchmaking) are aligned with ethical governance through the integration of tauhid, adl, khilafah, nubuwwah, and tazkiyah, which results in: increased productivity, greater market access, improved digital trust, and social empowerment (particularly for women and young people). The pentahelix orchestration is essential for developing skills, preparing for exports, and halal-value branding that incorporates maqāṣid al-sharī‘ah supports inclusive welfare (maslahah). The Islamic Pentahelix Digital Entrepreneurship Model (IPDEM), which includes value integration, collaborative governance, and sustainability mechanisms, is presented in the paper, and the implications for MSME policy are discussed in the conclusion. university-industry initiatives and halal-digital business practices aimed at generating balanced outcomes for profit, people, the environment, and maslahah.